Study on optimal concentration of uniconazole in rape coating agent and field effect of film coating on rape seed germination and subsequent growth of seedlings - QIU Jun; HU Jin; SONG Wen-jian; XIE Xiu-juan; HE Rong-miao (浙江大学学报. 农业与生命科学版)
Rape seed coating agents with different concentration uniconazole were used for film coating and their effects on rape of three cultivars were studied. Optimal concentration of uniconazole in coating agents was selected out based on comparison of germination rate, chlorophyll content, seedling height and dry weight of the grown-up seedlings. Field experiments showed that the selected rape coating agent with optimal concentration of uniconazole (Coat Ⅰ) effectively protected rape seedlings from damage by plant lice. It significantly reduced seedling height and main stem length, increased the number of leaves and green leaves at the three-leaf stage. It also had some effect in increasing width of main stem and seedling dry weight. Besides, the number of effective branches, pods per plant and seed harvest of three cultivars were also increased. Yield of Shuang 72 was increased by 18.9% as compared with the control which was not given film coating treatment. The results indicated that uniconazole could be used in preparation of seed coating agent in order to give rise to stronger seedlings of better quality and effectively resolve the problem of seedlings with high and slim main stems in rape production.